From Rome to Beijing: sacred spaces in dialogue - Greenberg, Daniel M.; Hara, Mari Yoko (East and West, 2024)
"From Rome to Beijing: Sacred Spaces in Dialogue, edited by Daniel M. Greenberg and Mari Yoko Hara, explores the relationship between Jesuit enterprise and Ming-Qing China in the seventeenth and eighteenth centuries. The Jesuit order's global corporation grew increasingly influential within the Chinese court after 1582, in no small part due to the two institution's shared interests in artistic and scientific matters. The paintings, astronomical instruments, spiritual texts and sacred buildings engendered through this encounter tell fascinating stories of cross-cultural communication and miscommunication. This volume approaches early modern East-West exchange as a site of cultural (rather than commercial) negotiations, where two sets of traditions and values intersected and diverged"--